2012
DOI: 10.1021/ja207510v
|View full text |Cite
|
Sign up to set email alerts
|

CO Oxidation Mechanism on CeO2-Supported Au Nanoparticles

Abstract: Density functional theory was used to study the CO oxidation catalytic activity of CeO 2 -supported Au nanoparticles (NPs). Experimental observations on CeO 2 show that the surface of CeO 2 is enriched with oxygen vacancies. We compare CO oxidation by a Au 13 NP supported on stoichiometric CeO 2 (Au 13 @CeO 2 -STO) and partially reduced CeO 2 with three vacancies (Au 13 @CeO 2 -3VAC). The structure of the Au 13 NP was chosen to minimize structural rearrangement during CO oxidation. We suggest three CO oxidatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

44
542
0
2

Year Published

2012
2012
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 512 publications
(588 citation statements)
references
References 82 publications
44
542
0
2
Order By: Relevance
“…Second, the HOMO of the Au SAC is spinminority dominated, and the spin-majority orbitals are totally Having clearly illustrated the critical step for O 2 activation by the Au cation on the Ni-doped TiO 2 (110) complex, we now investigate the kinetic processes of CO oxidation using the optimized NEB method. 46 Note that three CO oxidation mechanisms proposed by recent theoretical investigations 47,48 have been examined in the present study. We conrmed that the CO oxidation surprisingly prefers a quasi-Langmuir-Hinshelwood (L-H) process in this case, namely, CO can adsorb relatively weakly on the single Au atom close to the adsorbed O 2 molecule and the co-adsorbed molecules undergo a bimolecular reaction through the formation of a CO 2 precursor, which is subsequently released upon further activation, and the optimized substrate structure upon CO 2 desorption is shown as the initial state (IS) conguration in Fig.…”
mentioning
confidence: 89%
“…Second, the HOMO of the Au SAC is spinminority dominated, and the spin-majority orbitals are totally Having clearly illustrated the critical step for O 2 activation by the Au cation on the Ni-doped TiO 2 (110) complex, we now investigate the kinetic processes of CO oxidation using the optimized NEB method. 46 Note that three CO oxidation mechanisms proposed by recent theoretical investigations 47,48 have been examined in the present study. We conrmed that the CO oxidation surprisingly prefers a quasi-Langmuir-Hinshelwood (L-H) process in this case, namely, CO can adsorb relatively weakly on the single Au atom close to the adsorbed O 2 molecule and the co-adsorbed molecules undergo a bimolecular reaction through the formation of a CO 2 precursor, which is subsequently released upon further activation, and the optimized substrate structure upon CO 2 desorption is shown as the initial state (IS) conguration in Fig.…”
mentioning
confidence: 89%
“…In the case of supported, bare gold particles (as opposed to our ligands-on Au particles), Guzman et al observed reactive oxygen in the form of surface superoxide and peroxide species in CO oxidation. 41 Very recently, Kim et al 42 discussed three CO oxidation mechanisms on CeO 2 -supported Au nanoparticles on the basis of DFT calculations, including (1) CO oxidation by coadsorbed O 2 , (2) by lattice oxygen in CeO 2 , and (3) by O 2 bound to a AuÀCe 3þ anchoring site. While all these works refer to bare Au particles, in our case, the Au 25 particles are capped by thiolate ligands and there are possibly some major differences between the two systems.…”
Section: Articlementioning
confidence: 99%
“…It has been shown that Au 7 is the smallest Au cluster on rutile TiO 2 (110) with a measurable reaction rate for CO combustion [19]. The Au 11 model, although being a simplification of the nanometersized clusters on TiO 2 (110), appropriately mimics the active sites located at the nanogold/oxide interface where the oxidation process takes place [6,20]. The binding of the Au 11 cluster on the reduced TiO 2 (110) support entails a strong charge rearrangement at the metal/oxide contact (see Supporting Figure 1), the adsorption energy being −2.19 eV.…”
mentioning
confidence: 99%